A Randomized Control Trial to Assess the Efficacy and Safety of Manna Go Grains to Promote Growth, Immunity, and Well-Being in Children - Narayanaswamy, Murugan; Divya, B.; More, Rahul; Jadhav, Navnath; Ganu, Gayatri (International Journal of Child Health and Nutrition, 2023)
Objective: Nutrition in school-going children is crucial for their lifetime. India witnesses macro and micronutrient deficiencies in school-going children. The present study aims to evaluate the safety and efficacy of Manna go grains in promoting and improving growth, immunity, and well-being in children. Method: This was a 90-day randomized, controlled, parallel-arm clinical trial. 6-12 years old apparently healthy sixty-two children were randomized either into a test (Manna go grains plus milk) or a control group (milk) in a 1:1 ratio. We assessed changes in growth, immunity, appetite, and overall well-being before and after treatment. Result: The test group showed a significant increase in height, weight, height to age, and weight to age Z score and percentile, which was greater than the control group. There was significantly more improvement in VO2 max and appetite of children in the test group was observed as compared to the control group. A significant reduction in recurrent URTI episodes, sick days, recovery days, and missed school days was observed in the test group compared to the control. Memory questionnaire scores also increased significantly by 75% and 27.61% in the test and control groups. Test group parents reported significantly better growth, stamina, and immunity than the control group. There was clinically and statistically insignificant change in CBC, serum iron, serum calcium, and immunity markers like CD3, CD4, CD8, and IgG in both groups. Conclusion: Thus, Manna Go grains are thought to be a good candidate as a supplement for potentially stimulating growth and development in children and promoting their well-being.